Clinical Research of Scalp Acupuncture Combined with Rehabilitation Training Treating Patients with Cerebral Infarction in Recovery Period Based on1H-MRS - Yingping JIANG; Yifan ZHOU; Bo WANG; Shuting TANG; Yunfeng SUN (康复学报)
Objective:To explore the effect of different methods of scalp acupuncture for hemiplegia patients in cerebral infarction recovery period by using the magnetic resonance spectroscopy (MRS).Methods:Forty patients with cerebral infarction were randomly divided into four groups, 10 patients in each group, group A was treated by Yu's bilateral scalp acupuncture combined with rehabilitation training, group B, C and D were treated by the conventional Jiao's single ipsilateral scalp acupuncture combined with rehabilitation training, Yu's single ipsilateral scalp acupuncture combined with rehabilitation training and rehabilitation training respectively. Fugl-Meyer scores and MRS were used to evaluate the effect before and after the intervention of 15 days.Results:When comparing the difference in the Fugl-Meyer score within each group, group A was significantly better than group B and C (P<0.05); group A was obviously better than group D (P<0.01); the NAA/Cr of four groups were all increased with a significant difference (P<0.01); the Cho/Cr of group A and B was decreased evidently with statistical significance (P<0.01, P<0.05). With the comparison between groups of the NAA/Cr after treatment, group A was better than the other three groups with a significant difference (P<0.01); there was a statistical difference between group B and D, or between group C and D, (P<0.05); with the comparison between groups of the Cho/Cr after treatment, group A was better than group B and C with a statistical significance (P<0.05); group A was better than group D with a evidently statistical significance (P<0.01).Conclusion:Yu's bilateral scalp acupuncture combined with rehabilitation training can improve the motor function and cause the changes of metabolism in the corresponding brain of patients. The changes of metabolism may be related to the recovery of the motor function of the patients.